Pemanfaatan Geospasial Melalui Health and Demographic Surveillance System (HDSS) pada Pasien Tuberkulosis dalam Manajemen Obat - Diah Ayu Puspandari; Hermawati Setiyaningsih; Zafria Atsna; Tri Murti Andayani (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Tuberculosis (TB) is an infectious disease that causes a high mortality rate. Currently, Indonesia is the largest contributor to TB cases in the world. In 2019, the estimated number of cases was 845,000 cases, while case enrollment was 562,000. Thus, the Gap in the Case finding is high. As a result, innovation is needed in setting strategies to develop Regulations related to the national TB program, one of which is geospatial. This study aimed to provide an overview of geospatial utilization through HDSS in tuberculosis patients about drug management. Geospatial is an epidemiological approach that can be used to determine policies in accordance with conditions in an area. The research type is a quantitative study using secondary data from the Health and Demography Surveillance System (HDSS) of Sleman in 2016 and the Integrated TB Information System (SITT) of Sleman Regency in 2016. The analysis used descriptive analysis and geospatial mapping used Stata 15 and R software. Geospatial data shows that TB cases are concentrated in densely populated areas, such as Depok, Mlati, Ngaglik, and Gamping sub-districts. In addition, geospatial shows us the distance between the distribution of cases and the availability of health service facilities (puskesmas). The spread of cases is mostly found in the area around the health facilities, and low cases are in areas far from the health facilities. This condition possibly happens because case tracking is less affordable. Knowing the number and distribution of TB cases and the distribution of health care facilities can be used as a basis in the policy-making process, planning of the need for TB drugs, drug distribution, and priority interventions for TB services in a cost-efficiency.